THE COVALENCE OF THE BUSINESS-POWER-COMMUNITY TRIA - Nesterenko , Dmytro (Theory and Practice of Public Administration, 2020)
The article examines the system of relationships and functions of the institutions “business – authorities – society” at every turn of the triple helix, which have their own specifics, connected with the real situation in the state, and largely depends on the role played by each of the institutions in the sustainable development of the country, what competences it has. We have analyzed the relations “state-society”, “government-business”, “the society-business”. The model system of relations of the triad “business – authorities – society”. The identification of this triad, the complex structure of their relationship as a special sphere of scientific research is natural. Current time sets important for the future of the country, the problem of searching for a harmonious combination of interests of business, civil society and government.The scheme – triangle components of the system of relations in the triad “business – authorities – society”, demonstrates that it is based on, as the primary socio-economic relationships that are formed through a constructive social dialogue; the lack of it threatens the loss of the base of the triangle and, as a consequence, the prospects for the development of the system (this process is marked by a vertical arrow). Public policy can be effective only when the coincidence with the ideology and motives of the subjects themselves. The main function of ideology is to form the corresponding systems of values that are separated by society. Providing motivation is one of the main functions of state authorities, which is aimed at maintaining macroeconomic stability, a favourable external environment, the sustainability of the regulatory framework. Focused on the creation of new and optimization of already existing mechanisms of interaction of public authorities, business and civil society that will contribute to greater involvement of business and community to the processes of making public policy. the interaction between the state and business will influence not only the growth of economic indicators of the region and its social well-being, but also has a synergistic effect that improves the welfare of the nation as a whole.